РЕАЛИЗАЦИЯ МЕЖКУЛЬТУРНОЙ КОММУНИКАЦИИ НА УРОКЕ РУССКОГО ЯЗЫКА - Шынназарова, С.; Мамбеткаримова, Ф.Б. (SCIENCE and SOCIETY, 2020)
The article reveals the meaningful essence of the concept of "intercultural communication", examines the ways and means of its implementation in the process of the Russian language lesson.
Keywords: culture; communication; intercultural communication; methodology; language